Sarcasm in Social Media: A Figurative Language Analysis of Ryan Reynolds’ YouTube Videos - Azizi, Hafizul; Fitrawati, Fitrawati (Universitas Negeri Padang, 2024)
This research aimed to identify types and purposes of sarcasm used in Ryan Reynolds’ YouTube videos. Ryan Reynolds is famous actor who starred in various movies including Deadpool, Deadpool 2, Free Guy and Red Notice. This study uses the theory proposed by Camp (2011) and Kreuz (1991) regarding types and purposes of sarcasm respectively. This study uses descriptive method to analyse the utterances, as the source of the data. The data for this research were 37 sarcastic utterances taken from 15 videos from Ryan Reynolds’ YouTube channel. Three out of four types of sarcasm found after analyzing the data using Camp’s theory. They were propositional sarcasm (23 occurrences), illocutionary sarcasm (13 occurrences) and ‘like’-prefixed sarcasm (1 occurrence) with zero occurrence of lexical sarcasm. The second finding showed that all purposes of sarcasm occurs throughout the 37 data obtained. They were ‘to mock’ (15 occurrences), ‘to insult’ (13 occurrences), ‘to be funny’ (6 occurrences), ‘to criticize’ (2 occurrences) and ‘to show anger' (1 occurrence). It can be concluded that the most prominent type of sarcasm used in Ryan Reynolds’ YouTube videos is propositional sarcasm with 23 occurences and the most prominent used purpose of sarcasm is to mock with 15 occurrences.